1999
DOI: 10.1074/jbc.274.9.6003
|View full text |Cite
|
Sign up to set email alerts
|

JunB Forms the Majority of the AP-1 Complex and Is a Target for Redox Regulation by Receptor Tyrosine Kinase and G Protein-coupled Receptor Agonists in Smooth Muscle Cells

Abstract: To understand the role of redox-sensitive mechanisms in vascular smooth muscle cell (VSMC) growth, we have studied the effect of N-acetylcysteine (NAC), a thiol antioxidant, and diphenyleneiodonium (DPI), a potent NADH/NADPH oxidase inhibitor, on serum-, platelet-derived growth factor BB-, and thrombin-induced ERK2, JNK1, and p38 mitogen-activated protein (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
82
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 62 publications
6
82
0
Order By: Relevance
“…After immunoprecipitation of nuclear extracts with anti-Ref-1 rab- AP-1, an inducible transcription factor that recognizes a palindromic sequence (5Ј-TGACTCA-3Ј, phorbol 12-O-tetradecanoate-13-acetate-responsive element), is a homodimeric or heterodimeric leucine zipper complex containing the products of the fos and jun protooncogenes (45). AP-1 has been identified as an intermediary in PDGF-induced proliferation of SMCs (34). The activity of AP-1 is controlled not only by transcriptional and posttranscriptional mechanisms via increased rates of synthesis and decreased rates of degradation of fos and jun mRNA species, but also by translational and posttranslational (phosphorylation and redox regulation) mechanisms (7,40,45) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After immunoprecipitation of nuclear extracts with anti-Ref-1 rab- AP-1, an inducible transcription factor that recognizes a palindromic sequence (5Ј-TGACTCA-3Ј, phorbol 12-O-tetradecanoate-13-acetate-responsive element), is a homodimeric or heterodimeric leucine zipper complex containing the products of the fos and jun protooncogenes (45). AP-1 has been identified as an intermediary in PDGF-induced proliferation of SMCs (34). The activity of AP-1 is controlled not only by transcriptional and posttranscriptional mechanisms via increased rates of synthesis and decreased rates of degradation of fos and jun mRNA species, but also by translational and posttranslational (phosphorylation and redox regulation) mechanisms (7,40,45) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (27,34,37,39) from our lab and others have shown that PDGF can activate NAD(P)H oxidase in SMCs to produce O 2 Ϫ ⅐. This growth factorinduced NAD(P)H oxidase-dependent reactive oxygen species (ROS) generation leads to activation of transcription factors such as AP-1 and, consequently, cell proliferation (14,22,34,39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, thrombin stimulates ERK1/2, p38 mitogen activated protein kinase (p38MAPK) and JNK signaling, leading to induction of c-Fos and Jun-B, which combine to activate AP-1-mediated gene expression. Activation of all of these pathways is inhibited by NAC or DPI (Rao et al 1999). Similar to the signaling pathways utilized by AngII, catecholamines stimulate VSMC proliferation by ROS-dependent transactivation of the EGF receptor ).…”
Section: Vascular Smooth Muscle Proliferationmentioning
confidence: 99%
“…JunB has been shown to dimerize and transactivate AP-1 genes but can also act as a negative regulator of c-Jun for some genes (10,37). In cultured VSMCs, JunB has been detected in active AP-1 complexes in cells responding to receptor tyrosine kinase and G protein-coupled receptor agonists, and its induction is related to the production of reactive oxygen species (41). These findings together with our findings that Jun-and CREB-regulated genes are overrepresented in cerebral arteries from hypertensive animals indicate that signaling through AP-1 and CRE promoter elements may be particularly relevant in the arterial remodeling response.…”
Section: Discussionmentioning
confidence: 99%